2019
DOI: 10.18805/ajdfr.dr-886
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of bile tolerance and deconjugation ability of various Lactobacillus Casei group strains

Abstract: Lactobacillus casei group is commonly used as probiotics. Various factors affect their viability in gastrointestinal tract. Twenty two strains of Lactobacillus casei group were assessed for bile tolerance and deconjugation attribute. All strains had shown moderate activity at 0% bile concentration. At 1% bile concentration CSCC 2607 has shown highest growth while remaining Lactobacillus strains have shown fair growth. At 1.5% bile concentration only seven Lactobacillus strains showed gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…There are some studies where the authors have not found the activity of this enzyme in their L. casei strains [ 10 , 22 ]. However, there are others (including this study) in which good BSH activities have been detected [ 9 , 23 , 24 , 25 ]. The comparative values of the deconjugation percentage for sodium glycocholate and taurocholate can be observed in Table 4 .…”
Section: Resultsmentioning
confidence: 79%
“…There are some studies where the authors have not found the activity of this enzyme in their L. casei strains [ 10 , 22 ]. However, there are others (including this study) in which good BSH activities have been detected [ 9 , 23 , 24 , 25 ]. The comparative values of the deconjugation percentage for sodium glycocholate and taurocholate can be observed in Table 4 .…”
Section: Resultsmentioning
confidence: 79%
“…However, conditions such as low pH and osmotic stress can hinder the growth, viability, and fermentation processes of Lactobacillus spp. [28,29]. The LAB sets were exposed to pH 2.5 for different time intervals and examined for growth.…”
Section: Resultsmentioning
confidence: 99%